Synthesis of zwitterionic N-chlorohydantoins for antibacterial applications. Issue 23 (15th December 2018) - Li, Lingdong; Jin, Yanan; Zhou, Hao; Wang, Hande
Graphical abstract: Highlights: A carboxybetaine N -chlorohydantoins and a sulfobetaine N -chlorohydantoins were synthesized. The carboxybetaine N -chlorohydantoins displayed satisfactory antimicrobial efficacy. Biocidal activity of synthetic N -chlorohydantoins depends on the nature of zwitterionic head group. Abstract: Two novel zwitterionic N- chlorohydantoin biocides, containing an N- chlorohydantoin unit and a sulfobetaine unit or a carboxybetaine unit, were chemically synthesized and characterized. Using the quaternary ammonium N- chlorohydantoin as control, the antibacterial activity of synthetic zwitterionic N- chlorohydantoins was challenged and the antibacterial data showed that carboxybetaine N- chlorohydantoin exhibited distinctively higher biocidal efficacy than QA counterpart, while sulfobetaine N- chlorohydantoin displayed slightly inferior antimicrobial efficacy. Our results may inspire further exploration of more zwitterionic N- chlorohydantoin analogs for antibacterial application.